Ginkgolide C slows the progression of osteoarthritis by activating Nrf2/HO-1 and blocking the NF-κB pathway - Tianwen Ma; Lina Jia; Jinghua Zhao; Liangyu Lv; Yue Yu; Hongri Ruan; Xiaopeng Song; Hong Chen; Xin Li; Xin Li; Jiantao Zhang; Jiantao Zhang; et al. (Frontiers Media S.A., 2022)
Osteoarthritis (OA) is driven by chronic low-grade inflammation and subsequent cartilage degradation. OA is the most prevalent degenerative joint disease worldwide, and its treatment remains a challenge. The aim of this study was to explore the potential effects and mechanism underlying the anti-OA properties of ginkgolide C (GC). Protective effects of GC on hydrogen peroxide (H2O2)-treated rat chondrocytes were evaluated using ELISA, qPCR, western blot analysis, flow cytometry, ROS detection and immunofluorescence in vitro. Ameliorating effects of GC on cartilage degeneration in rats were evaluated through behavioral assays, microcomputed tomography, histopathological analysis, western blot analysis and ELISA in vivo. In vitro, GC treatment inhibited the release of pro-apoptotic factors induced by H2O2 and promoted the release of the anti-apoptotic proteins. In addition, GC decreased the expression of matrix metalloproteinase (MMP3 and MMP13), thrombospondin motifs 4 (ADAMTS4), and inflammatory mediators inducible nitric oxide synthase (iNOS), cyclooxygenase (COX-2), and SOX9 thereby inhibiting extracellular matrix (ECM) degradation. Mechanistically, GC exerts its anti-apoptotic and anti-inflammatory effects by upregulating the oxidative stress signaling Nrf2/HO-1 pathway and preventing p65 from binding to DNA. Similarly, In a rat model with post-traumatic OA (PTOA) induced by anterior cruciate ligament transection (ACLT), GC inhibited joint pain, cartilage destruction, and abnormal bone remodeling of subchondral bone. GC inhibited H2O2-induced chondrocyte apoptosis through Nrf2/HO-1 and NF-κB axis, exerted anti-inflammatory effects, and inhibited cartilage degeneration in rat OA. Our findings advanced the concept that GC may contribute to cartilage metabolism through anti-inflammatory and anti-apoptotic effects, and the identified GC is a potential therapeutic agent for the treatment of OA.